Musàhamàt 'Ulamà Nusantara fi Ibtidà'i Awzàn al Shi'ri al Arabiy wa Qowàfìh: Diràsah Uslùbiyyah 'an Makhtūtot al Ash'àr lil'ulamà al Minangkabawi - Hadi, Syofyan (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2020)
For centuries, Muslims in the Malay Archipelago have played a significant role in the development and advancement of Islamic civilization worldwide. Numerous scholars from the region have emerged and made substantial contributions to building Islamic civilization in various fields of Islamic knowledge. Among the most important contributions of scholars in the Malay Archipelago is their participation in the development of the Arabic language and literature. This can be seen from several books they have written, including in the field of linguistics and Arabic literature, to contribute to the development and dissemination of Arabic language and literature within the Islamic world, especially in the Malay Archipelago.Minangkabau scholars in some of their works have attempted to create new forms within the structure of Arabic poetry, such as the poetic creations found in the works of Sheikh Muhammad Sa'ad Munka, Sheikh Abdul Hamid bin Ahmad Al-Khatib Al-Manangkabawi, Sheikh Ismail Al-Manankabawi, and Sheikh Muhammad Said Bonjol. In addition to producing works with very high aesthetics, these Minangkabau scholars also introduced creative aspects in the composition of their poetry, especially in terms of rhythm and rhyme, which were not even brought forth by classical Arab poets considered the golden age of Arabic literature itself.Therefore, the main issue in this article is the creative forms of expression of Nusantara scholars in the rhythm and rhyme of the verses they create. The author employs Ahmad Shaib's Uslub theory, which states that every poet has a distinct style in expressing their ideas reflected in their choice of words, sentence structures, metaphorical language, rhythm, and rhyme.